Retirement Decisions - Zhou, P (My University, 2011)
Using the Household, Income and Labour Dynamics in Australia (HILDA) Survey, I find that gender effects on the retirement decision are less pronounced than in previous studies, which emphasize financial incentives for males and family reasons for females. Retirement decisions depend on the trade-off between household retirement wealth and individual career length. I estimate the intertemporal substitution on elasticity of the retirement decision. Neither males nor females respond strongly to financial incentives, but do to job disutility.
Keywords: Ageing -- Retirement; Employment -- Exit from employment (Retirement/Redundancy); Ageing; Labour market; Ageing; Employment; Exit from employment (Retirement/Redundancy); Retirement; Employment and unemployment; Ageing